(Un)dressing masculinity: The body as a site of ethno-gendered resistance. (May 2015) - Kachtan, Dana; Wasserman, Varda
This article explores the ways in which the aesthetics of employees' bodies are used as a site of control and resistance, processes which are activated through ethnic and gendered practices. By exploring three resistance strategies used by Israeli combat soldiers, we demonstrate the construction of competing identities of military masculinity. We demonstrate how, by activating a process of self-ethnicization, Israeli soldiers use an ethnic identity that empowers them and challenges the 'appropriate' professionalism expected from them. This process illuminates the interrelations between ethnic and masculine identities, and emphasizes the dynamic and fluid nature of the constructing of identities within organizations.